Mapping long-term temporal change in imperviousness using topographic maps - Miller, James D.; Grebby, Stephen (Elsevier, 2014)
Change in urban land use and impervious surface cover are valuable sources of information for determining the environmental impacts of urban development. However, our understanding of these impacts is limited due to the general lack of historical data beyond the last few decades. This study presents two methodologies for mapping and revealing long-term change in urban land use and imperviousness from topographic maps. Method 1 involves the generation of maps of fractional impervious surface for direct computation of catchment-level imperviousness. Method 2 generates maps of urban land use for subsequent computation of estimates of catchment imperviousness based on an urban extent index. Both methods are applied to estimate change in catchment imperviousness in a town in the South of England, at decadal intervals for the period 1960–2010. The performance of each method is assessed using contemporary reference data obtained from aerial photographs, with the results indicating that both methods are capable of providing good estimates of catchment imperviousness. Both methods reveal that peri-urban developments within the study area have undergone a significant expansion of impervious cover over the period 1960–2010, which is likely to have resulted in changes to the hydrological response of the previously rural areas. Overall, results of this study suggest that topographic maps provide a useful source for determining long-term change in imperviousness in the absence of suitable data, such as remotely sensed imagery. Potential applications of the two methods presented here include hydrological modelling, environmental investigations and urban planning.